2021
DOI: 10.1111/aos.14886
|View full text |Cite
|
Sign up to set email alerts
|

Three‐year effectiveness and safety of the XEN gel stent as a solo procedure or in combination with phacoemulsification in open‐angle glaucoma: a multicentre study

Abstract: Purpose: To assess the 3-year effectiveness and safety of the XEN gel stent implanted ab interno in open-angle glaucoma (OAG). Methods: This study was a multicentre, retrospective chart review of consecutive patients with OAG who underwent ab-interno gel stent placement alone or combined with phacoemulsification between 1 January 2014 and 1 October 2015. Outcome measures included mean changes in intraocular pressure (IOP) and IOP-lowering medication count from medicated baseline at 1, 2, 3 (primary outcome) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 15 publications
5
48
2
1
Order By: Relevance
“…We found that a failed trabectome surgery does not affect the outcomes, including postoperative IOP, postoperative medication score, side effects, revision rate, repeat surgery rate, and success rate, of a subsequent XEN45 gel stent implantation. Our findings, which were consistent with those of previous studies, provided further evidence for the efficacy of XEN gel stent implantation in reducing both IOP and medication scores while retaining a favorable safety profile [10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that a failed trabectome surgery does not affect the outcomes, including postoperative IOP, postoperative medication score, side effects, revision rate, repeat surgery rate, and success rate, of a subsequent XEN45 gel stent implantation. Our findings, which were consistent with those of previous studies, provided further evidence for the efficacy of XEN gel stent implantation in reducing both IOP and medication scores while retaining a favorable safety profile [10][11][12][13][14][15][16].…”
Section: Discussionsupporting
confidence: 92%
“…The implant has a small lumen, which assures a moderate drainage of the aqueous humor into the subconjunctival space with minimal side effects, such as hypotony. Several researchers have reported on their favorable safety profile, along with the promising IOP-lowering potential [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Gel stent XEN45 was introduced in its current form with 45 micrometers lumen several years prior to the PreserFlo Microshunt, hence, several studies have been published on its safety and efficacy. In these studies, the observation period ranged from 6 months [6] to 3 years [7,8], and IOP reduction success rates were comparable to the Basel groups.…”
Section: Discussionmentioning
confidence: 90%
“…Die IOD-Werte in mmHg präoperativ/am 1. postoperativen Tag/Woche 1/Monate 1/3/6/ 12 waren jeweils für PreserFlo Microshunt und XEN45 wie folgt: 23,6 vs. 24,9; 9,0 vs. 8,9; 11,4 vs. 10,6; 13,0 vs. 18,3; 16,8 vs.15,1; 15,9 vs. 15,0; 15,4 vs. 14,5. Die Anzahl der IOD-senkenden Medikamente war postoperativ zwischen den 2 Gruppen ausbalanciert; die Anzahl der nachträglichen Interventionen war höher in der XEN45-( 13) als in der PreserFlo-Microshunt-Gruppe (7).…”
Section: Methodsunclassified
“…Eight non-randomized studies compared the outcomes between XEN standalone and XEN combined with cataract surgery. Six studies directly noted that there was no significant difference between the two groups (9,19,43,53,63,81). Fea et al (12) demonstrated that compared with the combined group, more patients in the standalone group achieved complete success with IOP ≤14 mmHg and no antiglaucoma medications (41.6 vs. 22.9%, respectively; p = 0.03).…”
Section: Comparison With Other Surgeriesmentioning
confidence: 99%